Regulatory T‐cell‐derived interleukin‐15 shapes cytotoxic T cell memory. Issue 1 (8th December 2022) - Geginat, Jens; Granucci, Francesca
Abstract: It is well known that regulatory T‐cells (Tregs) are required to prevent autoimmunity, but they may also have some less‐well understood immune‐stimulatory effects. In particular, in CD8 + T‐cell responses Tregs select high‐affinity clones upon priming and promote memory by inhibiting inflammation‐dependent generation of short‐lived effector cells. In the current issue of the European Journal of Immunology [Eur. J. Immunol. 2023. 53: 2149400 ], Madi et al. report the surprising finding that human and murine FOXP3 + Tregs are a physiologically relevant source of IL‐15, a homeostatic cytokine that promotes antigen‐independent maintenance of CD8 + memory T‐cells. In mice that lack IL‐15 selectively in FOXP3 + Tregs the authors show that the composition of the CD8 + T‐cell memory pool is altered in the absence of Treg‐derived IL‐15, since a subset of terminally effector memory cells is drastically reduced. Otherwise Treg‐derived IL‐15 is dispensable for antiviral immune responses and the generation of anti‐viral CD8 + memory T‐cells. These findings add to our understanding of the multifaceted role of Tregs in immune responses, and how IL‐15 derived from different cellular sources maintains anti‐viral T‐cell memory. Abstract : Regulatory T‐cell‐derived IL‐15 shapes cytotoxic T cell memory (Commentary) FOXP3 + Tregs suppress T‐cell responses, including the priming of low‐avidity CD8 + T‐cell responses. Madi et al. report that FOXP3 + Tregs could trans‐present IL‐15. Intriguingly, Treg‐derived IL‐15 supported the homeostasis of terminally differentiated CD8 + memory T‐cells. This provocative study challenges our view on memory T‐cell maintenance, and on the functions of FOXP3 + Tregs.